Association between Body Mass Index and Depressive Symptoms among Adolescent Females in Baghdad, AlKarkh during 2022 - Alkabban, Masarrah M.; Alkhazrajy, Lujain A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Due to their high prevalence rates, adolescent obesity and depression are among the most renowned public health concerns globally. Obesity is considered the leading cause of morbidity and death in Iraq in 2019. There is scarce research and surveys regarding the relation between BMI and depression, especially in young Iraqi females. Objectives: To explore the level of depression among adolescent girls and to determine its association with body mass index in the study group. Methods: Beck’s depression inventory questionnaire was used in 11 high schools for girls that were selected randomly from the schools in Baghdad/AlKarkh from 1st of January 2023 till the end of May 2023. A sample of 350 adolescent girls was included in the study. The height and weight of each participant were measured, and BMI was calculated. Tables and graphs were constructed to describe the data. The Chi-square test was used to test the association between categorical data. A P value of less than 0.05 was considered statistically significant. Results: Of the studied group, 14% were underweight, 59% normal weight, 21% overweight, and 6% obese. As for mood status, 16% had mild mood disturbance, 24.3% had borderline clinical depression, 13.4% had moderate depression, and 3.1% had severe depression. Severe depressive symptoms were found in 15% of obese girls, significantly higher than those among overweight (1.4%), normal weight (2.4%), and underweight (3.4%) individuals. Conclusions: There was a significant association between obesity and severe depression, and a positive significant correlation between BMI and depression.